Micro-scale variation-tolerant exponential tracking energy harvesting system for wireless sensor networks. Issue 3 (March 2015) - Eltaliawy, Ayman; Mostafa, Hassan; Ismail, Yehea
Abstract Self-powered stand-alone electronic systems, targeting low power applications, are the future of power management. In wireless sensor networks (WSNs) and implantable devices, battery replacement is expensive and power management of these systems is essential. Energy harvesting is considered one of the main power management methods that scavenge energy from the ambient resources that are available and abundant. They take the advantage of minimizing the maintenance costs as well as saving area (Penella-Lopez and Gasulla-Forner, 2011 [1]). This paper presents a new tracking technique for maximum power harvesting of solar energy using a micro-scale photovoltaic cell. The new design is based on the analytical derivation of the system equations. The power converter used is a tree topology charge pump, the control circuit is a low frequency voltage controlled oscillator (VCO), and the energy storage element is an output super-capacitor. The system is designed using TSMC 65 nm technology node. Typical power efficiency of the proposed circuit reaches 63% where the proposed design is targeting indoors and outdoors light intensities at zero load condition. The maximum power consumption of the harvester reaches <alternatives><inline-graphic xlink:href="ark:/27927/pgh3xhrqn0m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />170μW</alternatives>.